2020
DOI: 10.4269/ajtmh.19-0493
|View full text |Cite
|
Sign up to set email alerts
|

Systematic, Point-of-Care Urine Lipoarabinomannan (Alere TB-LAM) Assay for Diagnosing Tuberculosis in Severely Immunocompromised HIV-Positive Ambulatory Patients

Abstract: Point-of-care urine-lipoarabinomannan (LAM) Alere Determine TB-LAM assay has shown utility diagnosing tuberculosis (TB) in HIV-positive, severely immunocompromised, TB-symptomatic patients. We assessed LAM results in severely immunocompromised patients, who had LAM systematically performed at new or follow-up HIV consultations. This was a prospective, observational study on consecutive ambulatory, > 15-year-old HIV-positive patients with CD4 < 100 cells/μL in Mozambique. Clinical assessments and LAM were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…According to the bivariate boxplot, we found the source of considerable heterogeneity. The heterogeneity may be resulted from the points outside the circle, thus we reviewed papers these points represent in Figure 3 , 20 , 64 , 79 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the bivariate boxplot, we found the source of considerable heterogeneity. The heterogeneity may be resulted from the points outside the circle, thus we reviewed papers these points represent in Figure 3 , 20 , 64 , 79 .…”
Section: Resultsmentioning
confidence: 99%
“…64 Huerga reported the highest sensitivity (81%) and specificity (100%), but only patients with HIVpositive and CD4+ <100 cells/μl were enrolled. 79 Nonetheless, the current study has a few limitations. In terms of research design and quality assessment, not all selected studies are included in a random or continuous manner, which may result in a lack of reasonable sampling methods.…”
Section: Co-infection Provides Reciprocal Advantages To Both Mtb Andmentioning
confidence: 86%
See 1 more Smart Citation
“…Cross-reactions between LAM and NTM antigens have been previously observed in patients with NTM disease (Bjerrum et al, 2020, De et al, 2020, Huerga et al, 2020, Nel et al, 2017. LAM encompasses a large family of related molecules which are expressed by all mycobacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have been performed to assess the impact of AlereLAM on time to initiation of TB treatment in an outpatient setting. 11 , 12 , 13 The multi-centre TB-NEAT trial performed AlereLAM on biobanked urine samples and concluded that AlereLAM results would have no impact on decreasing time to initiation of TB treatment if chest X-ray facilities are available on-site and where rates of empiric TB treatment are high. 13 Despite a high burden of TB in our study’s community and generally higher healthcare resources in South Africa than some other comparable high-burden settings, the clinics in this study do not have access to on-site chest X-ray.…”
Section: Discussionmentioning
confidence: 99%